Values and challenges in the assessment of coprophilous fungi according to the IUCN Red List criteria: the case study of Poronia punctata (Xylariales, Ascomycota). (20th September 2020) - Ceci, Andrea; Angelini, Paola; Iotti, Mirco; Lalli, Giorgio; Leonardi, Marco; Pacioni, Giovanni; Perrone, Luigi; Pioli, Silvia; Siniscalco, Carmine; Spinelli, Veronica; Venturella, Giuseppe; Wagensommer, Robert P.; et al.
Abstract: Coprophilous fungi are specialized microorganisms, playing key roles in ecosystems and in several other contexts, whose protection requires more substantial efforts. This paper aims to highlight and discuss valuable and critical aspects faced during the process of the threat status assessment of Poronia punctata, providing inspirations for future conservation actions.